Performance enhancement of poly (vinylidene fluoride-co-hexafluoro propylene)/polyethylene oxide based nanocomposite polymer electrolyte with ZnO nanofiller for dye-sensitized solar cell - Zebardastan, N.; Khanmirzaei, M.H.; Ramesh, S.; Ramesh, K. (Elsevier, 2017)
Nanocomposite polymer electrolytes (NCPEs) were prepared by blending poly (vinylidene fluoride-co-hexafluoro propylene) copolymer (PVdF-HFP) and polyethylene oxide (PEO) polymers and incorporation of ZnO inorganic nanofiller (PVdF-HFP:PEO:EC:PC:NaI:I2:ZnO). The highest ionic conductivity value of 8.36 mS cm−1 was recorded when 3 wt.% of ZnO inorganic nanofiller was incorporated into the NCPE system. Temperature-dependant ionic conductivity behaviour of NCPEs was analysed and proven to follow the Arrhenius thermal activated model. Structural studies of NCPEs were carried out using X-ray diffraction (XRD) and Fourier transform infrared (FTIR) spectroscopy analysis. NCPEs were used to fabricate Dye-sensitized solar cells (DSSCs). Enhancements in the solar light to electricity conversion efficiency (η) of DSSCs were observed in the presence of ZnO inorganic nanofiller in the NCPE system and NCPE with 3 wt.% ZnO represented the highest η of 7.33% under full sun irradiation.